Digitalization of Play Activities and Games: Artificial Intelligence in Early Childhood Education - Umi Masturoh; Ika Irayana; Firdausi Nuzula Adriliyana (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2024)
This research study discusses the integration of artificial intelligence (AI) in Early Childhood Education (PAUD) units to improve play and game activities for children as well as innovation in implementing AI-based learning. AI technology has very good prospects and potential in changing teaching and learning activities in educational units with its ability to think and learn like humans, understand human feelings, find solutions in complex decision making, and so on. However, this is sometimes not in line with the application of AI in early childhood education units which are still in their early stages, especially in developing countries like Indonesia. The method used in this research is qualitative research, the data collection technique is from various journal articles about the benefits and impact of AI on early childhood play and play activities. With the support of AI, PAUD units can improve the results of their teaching and learning activities by facilitating more diverse play experiences, increasing operational efficiency, monitoring children's play and play results in real time. Although progress in the application of AI has been seen, there appear to be challenges and shortcomings, including limited AI research in fields outside of STEAM (Science, Technology, Engineering, Arts, and Mathematics), the lack of AI theories and models in play and gaming activities, and resistance in adopting AI in a child's play activities. It is important for PAUD units to integrate AI more optimally in the process of playing and playing activities for children, as well as providing training to educators, education staff and PAUD students to optimize the education system in the future